Multi‐proxy study of Holocene environmental change and human activity in the Central Apennine Mountains, Italy. (3rd January 2013) - Brown, A. G.; Hatton, J.; Selby, K. A.; Leng, M. J.; Christie, N.
Abstract This paper describes a multi‐proxy palaeoecological investigation undertaken in conjunction with an archaeological survey of the Upper Sangro Valley in the Abruzzo National Park, Central Italy. Despite being a biodiversity hotspot and regarded as a near‐pristine area, the pollen, spore and diatom data all show major changes in the vegetation extending to over 2000 m a.s.l. during the mid to late Holocene. Although there are changes in ecological composition earlier in the Holocene they are different in type and magnitude from the changes which began about 800 cal a BC. The pollen and diatom evidence do not correlate well with regional palaeoclimate data, or on‐site isotopic evidence, but do appear to be related to Samnite (later Iron Age) clearance and upland grazing associated with transhumance and later annexation (and centuriation) of the lower slopes by Roman surveyors. The greatest change in vegetation was during the period c. AD 500–600 and corresponds with the Byzantine–Gothic Wars, and Lombard–Carolingian settlement reorganization into nucleated hilltop settlements which managed upland grazing. This pattern of intensive land use at all altitudes persisted until the early 20th century and only changed following rural depopulation after World War II. These data illustrate how cultural factors had a profound effect on this mountainous region which, in this case, far outweighed the effects of climatic fluctuations which are known to have occurred from both this study area and the region. Copyright © 2012 John Wiley & Sons, Ltd.